2009
DOI: 10.1525/cond.2009.080112
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Plasma Metabolites to Predict Weekly Body-Mass Change in Red Knots

Abstract: Resumen. Los individuos de la especie Calidris canutus migran largas distancias, se reproducen en la tundra a altas latitudes en el Ártico e invernan a lo largo de las costas templadas y tropicales. La tasa de abastecimiento antes del vuelo es la principal determinante del éxito de migración. Sin embargo, estas tasas de abastecimiento son imposibles de determinar debido a que los individuos de C. canutus no son recapturados con facilidad. Estos problemas pueden ser minimizados con la estimación de los cambios … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…An indirect estimate of fuelling rate in birds caught only once is provided by plasma metabolite concentrations (Dietz et al 2009;Guglielmo et al 2005;Jenni and Schwilch 2001;Jenni-Eiermann and Jenni 1994;Schaub and Jenni 2001). High concentrations of triglycerides and low concentrations of ß-hydroxybutyrate indicate that the birds are in a resorptive state and gaining mass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An indirect estimate of fuelling rate in birds caught only once is provided by plasma metabolite concentrations (Dietz et al 2009;Guglielmo et al 2005;Jenni and Schwilch 2001;Jenni-Eiermann and Jenni 1994;Schaub and Jenni 2001). High concentrations of triglycerides and low concentrations of ß-hydroxybutyrate indicate that the birds are in a resorptive state and gaining mass.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic state of birds was determined from the concentration of certain metabolites in plasma (Dietz et al 2009;Guglielmo et al 2002;Jenni and Schwilch 2001;Jenni-Eiermann and Jenni 1991;Schaub and Jenni 2001;Seaman et al 2005). In particular, the plasma concentrations of triglycerides and b-hydroxybutyrate provided an estimate of the rate of body-mass change (Jenni-Eiermann and Jenni 1994).…”
Section: Plasma Metabolitesmentioning
confidence: 99%
“…For example, Smith and McWilliams (2009) found that plasma lipid metabolite levels reflected the fattening rates of small passerines fed a synthetic diet within the previous few hours, whereas Seaman et al (2005) found that these metabolites could predict body mass changes over the past few days in Western Sandpipers Calidris mauri. Although several other studies have been performed using these time scales, to the best of our knowledge, only the study by Dietz et al (2009) clearly reported the usefulness of the technique for longer periods (but see Williams et al 1999). …”
Section: Introductionmentioning
confidence: 99%
“…Jenni-Eiermann and Jenni 1994;Williams et al 1999;Dietz et al 2009). For example, the use of triglycerides and b-hydroxybutyrate has been validated as an indicator of fuel deposition rate in insectivorous, granivorous, and frugivorous birds (Williams et al 1999;Schaub and Jenni 2001;Jenni and Schwilch 2001;Guglielmo et al 2005;Seaman et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Capture stress could also have altered some of these parameters (Romero and Romero, 2002;Lynn and Porter, 2008); however, we attempted to minimize this by processing blood samples within 3 hr of collection (Dietz et al, 2009). One limitation of this study is the lack of data on sex and age of individuals.…”
mentioning
confidence: 99%